Comparison of the somatic state and the level of motor performance of boys between the ages of seven and fifteen in the Olomouc region (Czech Republic) and in Opole (Poland) - Miroslav Kopecký; Cezary Kusńierz; Kateřina Kikalová; Jiří Charamza (Palacky University, 2013)
BACKGROUND: Recent years have seen a decrease in habitual movement activity in children and youth, which is being replaced by the predominance of a sedentary lifestyle. A reflection of these negative trends is also seen in the decrease in motor performance. OBJECTIVE: The aim of this research is to analyze the level of the motor skills of contemporary 7 to 15 year olds in Olomouc and in Opole and to compare the physical parameters of Olomouc and Opole boys with the 6th Nation-Wide Anthropological Survey of Children and Adolescents 2001 Czech Republic (the 6th CAV 2001). METHODS: The research was carried out in both the Olomouc (695 boys) and Opole (313 boys) regions. For the diagnostics of the level of the motor performance of the boys, standardized motoric tests were used: the standing long jump with legs together, one-minute sit-ups, the 4 × 10 meter shuttle run, and throwing a medicine ball using both hands, as well as the testing battery UNIFITTEST (6–60). For the statistical evaluation of the results, Student’s t-test, Z-scores and the non-parametric χ2-test were used. RESULTS: The results have shown that, in height and weight, both boys from Olomouc and from Opole are in accordance with parameters, which correspond also to the reference data of the 6th CAV 2001. An identical performance level was reached by both sets of boys in the 4 × 10 m shuttle run and in the standing long jump with legs together. In throwing the medicine ball with both hands, the Olomouc boys scored lower than the boys from Opole. During the period of their earlier school years, Olomouc boys scored higher in the one-minute sit-up test. The evaluation of individual motoric performance of boys in accordance with the testing battery UNIFITTEST (6–60) showed overall that 39% of the Olomouc boys and 42% of the Opole boys had less than average or even below average motoric performance levels. A comparison of the tested results of contemporary Olomouc and Opole boys with referential data for the Olomouc boys dating to 2001 and 2002 indicated a decrease in the speed, endurance and strength of their abdominal musculature and the dynamic-explosive capability of their upper and lower extremities. CONCLUSIONS: The decrease in the motoric performance level of Olomouc and Opole boys probably reflects a decrease in habitual movement activity and the prevalence of a sedentary lifestyle.